Correction: Posterior Fixation and Fusion (PFF) versus Combined Anterior and Posterior Fixation and Fusion (CAPFF) for type B and C thoracolumbar spine injuries: a systematic review and meta-analysis - Mkochi, Vincent L.; Sharma, Hari; Gonzalez, Alexis G; Wu, Hao-Hua; Harvard Global Orthopaedic Collaborative (HGOC) (Tufts University Tisch Library, 2026)
Springer Open.